Ischemic preconditioning enhances aerobic adaptations to sprint-interval training in athletes without altering systemic hypoxic signaling and immune function - Paradis-Deschênes, P.; Joanisse, D. R.; Mauriège, P.; Billaut, F. (Frontiers in Sports and Active Living, 2020)
Optimising traditional training methods to elicit greater adaptations is paramount for athletes. Ischemic preconditioning (IPC) can improve maximal exercise capacity and up-regulate signaling pathways involved in physiological training adaptations. However, data on the chronic use of IPC are scarce and its impact on high-intensity training is still unknown. We investigated the benefits of adding IPC to sprint-interval training (SIT) on performance and physiological adaptations of endurance athletes. In a randomized controlled trial, athletes included eight SIT sessions in their training routine for 4 weeks, preceded by IPC (3x5-min ischemia/5-min reperfusion cycles at 220 mmHg, n=11) or placebo (20 mmHg, n=9). Athletes were tested pre-, mid- and post-training on 30-sec Wingate test, 5-km time trial (TT) and maximal incremental step test. Arterial O2 saturation, heart rate, rate of perceived exertion and quadriceps muscle oxygenation changes in total hemoglobin (DeltanTHb]), deoxy-hemoglobin (Delta[HHb]) and tissue saturation index (DeltaTSI) were measured during exercise. Blood samples were taken pre- and post-training to determine blood markers of hypoxic response, lipid-lipoprotein profile and immune function. Differences within and between groups were analyzed using Cohen`s effect size (ES). Compared to PLA, IPC improved time to complete the TT (Mid vs. Post: -1.6%, Cohen`s ES±90% confidence limits -0.24, -0.40;-0.07) and increased power output (Mid vs. Post: 4.0%, ES 0.20, 0.06;0.35), Delta[THb] (Mid vs. Post: 73.6%, ES 0.70, -0.15;1.54, Pre vs. Post: 68.5%, ES 0.69, -0.05;1.43), Delta[HHb] (Pre vs. Post: 12.7%, ES 0.24, -0.11;0.59) and heart rate (Pre vs. Post: 1.4%, ES 0.21, -0.13;0.55, Mid vs. Post: 1.6%, ES 0.25, -0.09;0.60). IPC also attenuated the fatigue index in the Wingate test (Mid vs. Post: -8.4%, ES -0.37, -0.79;0.05). VO2peak and maximal aerobic power remained unchanged in both groups. Changes in blood markers of the hypoxic response, vasodilation, and angiogenesis remained within the normal clinical range in both groups. We concluded that IPC combined with SIT induces greater adaptations in cycling endurance performance that may be related to muscle perfusion and metabolic changes. The absence of elevated markers of immune function suggests that chronic IPC is devoid of deleterious effects in athletes, and is thus a safe and potent ergogenic tool.